Pelatihan Batik Ecoprint Sebagai Sarana Pengembangan Ketrampilan Bagi Kader PKK Di Desa Kaliurip Kabupaten Purworejo - Pramudya Elentika; Eny Setiyowati (Journal of Conflict and Social Class (JCSC), 2026)
The purpose of this community service is to empower PKK cadres by developing ecoprint batik skills utilizing existing plants into new products. The method of implementing the activity is through the following stages: 1) observation, 2) counseling, 3) training, 4) evaluation. The target of the community service activity is PKK cadres. The data collection technique uses interviews. The conclusion of the ecoprint batik activity provides new skills for PKK cadres. Analysis of the results of interviews with training participants stated that making ecoprint batik is easy to do with low costs and good results. Ecoprint batik has different motifs/patterns and techniques from other batik producers. Participants were very enthusiastic and eager to develop batik production in Kaliurip Village, Purworejo Regency, as a form of village income. Analysis of the results of interviews with training participants stated that making ecoprint batik is easy to do with low costs and good results.